Convergence Analysis of a Continuous-Time Distributed Gradient Descent Algorithm - Zhang, Mengyao; Liu, Xinzhi; Liu, Jun (IEEE control systems letters, 2021)
There are various methods designed for solving the distributed optimization problem with only local computation and communication. This letter discusses a continuous-time and distributed version of the gradient descent method for solving the distributed optimization problem. We prove that the convergence rate of this method matches those of the centralized gradient descent method and distributed consensus.